Incorporating circulating tumor DNA detection to radiographic assessment for treatment response in advanced EGFR-mutant lung cancer. (January 2022) - Kok, Peey-Sei; Lee, Kirsty; Lord, Sally; John, Thomas; Marschner, Ian; Wu, Yi-Long; Mok, Tony S.K.; Lee, Chee Khoon
Highlights: Radiologic response and undetectable ctDNA are independently prognostic of PFS. CtDNA clearance discriminates patients' survival in those with stable disease. In those with early PR and undetectable ctDNA, 93% had ongoing PR. Parallel ctDNA and RECIST measurements improve accuracy of tumor assessment. Abstract: Purpose: Response Evaluation Criteria in Solid Tumors (RECIST) has limitations but remains the conventional approach for tumor assessments. We explored whether circulating tumor DNA (ctDNA) can be incorporated into RECIST to provide a more robust measure of tumor response in advanced EGFR- mutant NSCLC. Patients and methods: In FASTACT-2, patients with advanced NSCLC received platinum/gemcitabine intercalated with erlotinib or placebo. EGFR mutation (tumor and plasma ctDNA) was detected using cobas v2. Patients selected for this hypothesis-generating analysis had EGFR mutations (on either tumor or plasma) at baseline and evaluable week 8 plasma EGFR . Week 8 ctDNA and radiologic response status were correlated with survival using landmark cox regression analyses. Results: Of the original 451 patients, 86 (19.1%) were eligible for this analysis. 73% (n = 63) had detectable ctDNA at baseline . At week 8, 40% (n = 34) had radiologic partial response (PR), 60% (n = 52) had stable disease (SD); 80% (n = 69) had a ctDNA response (undetectable ctDNA). In patients who had initial PR and undetectable ctDNA, 93% (28/30) had ongoing PR subsequently at week 16. The median duration of response was 14.9 months. In patients with SD and undetectable ctDNA at week 8, 28% had radiological PR at week 16. Amongst those with PR at week 8, survival outcomes for those with undetectable vs detectable ctDNA were not statistically significant (PFS HR 0.49, 95%CI 0.16–1.48, p = 0.21; OS HR 0.39, 95%CI 0.13–1.19, p = 0.10). Amongst those with SD at week 8, there was significantly longer survival for those with undetectable vs detectable ctDNA (PFS HR 0.27, 95% CI 0.13–0.57, p < 0.0001; OS HR 0.40, 95% CI 0.20–0.80, p = 0.009). Conclusion: In patients with SD, undetectable ctDNA at week 8 correlated with survival improvement. Both radiologic and ctDNA responses are prognostic of PFS. Incorporation of ctDNA with RECIST may improve tumor response assessment in EGFR -mutant NSCLC.